Suid-Afrika en die beslegting van gewapende konflik in Afrika sedert 1994 - Abel Esterhuyse (Acta Academica, 2002)
An understanding of the anatomy of conflict is essential to any effort to resolve armed conflict. This implies that South Africa should take cognisance of the causes of conflict, its progression and the ways in which it can be ended, before the country can be meaningfully involved in conflict resolution in Africa. Her foreign and domestic policies and her intention to keep South African involvement within the framework of regional and international organisations underpin her involvement. Thus far, South African involvement has been characterised by neutrality, an emphasis on diplomatic solutions, ex-president Mandela’s personification thereof and the avoidance of high-risk peace keeping operations.